Enhancing nutrient recovery and compost maturity of coconut husk by vermicomposting technology. (May 2016) - Swarnam, T.P.; Velmurugan, A.; Pandey, Sanjay Kumar; Dam Roy, S.
Highlights: Earthworm could convert coconut husk mixed with animal manure into a valuable compost. Mixing of animal manure with coconut husk increased the relative nutrient recovery. Index value for maturity parameters were derived for composting of coconut husk. Manurial value of coconut husk compost improved by pig slurry substitution. Abstract: Vermicompost was prepared by five different treatments from relatively resistant coconut husk mixed with either pig slurry or poultry manure. The recovery of vermicompost varied from 35% to 43% and it resulted in significant increase in pH, microbial biomass carbon, macro and micro nutrients concentration. Among the treatments highest relative N (1.6) and K (1.3) recovery were observed for 20% feedstock substitution by pig slurry while poultry manure substitution recorded highest P recovery (2.4). Compost maturity parameters significantly differed and well correlated. The characteristics of different treatments established the maturity indices as C/N 15–20; Cw < 1.8; Cw/Norg < 0.55; Lignin < 10–12; CHA/CFA > 1.5 and HI > 15.0. The manurial value of the coconut husk compost was improved by feedstock substitution with pig slurry (80:20). The results revealed the technical feasibility of converting coconut husk into valuable compost by feedstock substitution with pig slurry.